Building effective teams for sustainable performance: A case study in public sector governance - Sindi Nofia Puji Lestari; Boge Triatmanto (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Employee performance is influenced by various factors, including teamwork, communication, and work environment. These elements are critical in shaping the efficiency and productivity of employees within an organization. This study aims to analyze the simultaneous and dominant effects of teamwork, communication, and work environment on employee performance at the Dinas Perpustakaan dan Kearsipan (Library and Archives Office) in Kota Probolinggo. Methods: This research employs a quantitative approach using regression analysis to examine the relationship between independent variables (teamwork, communication, and work environment) and the dependent variable (employee performance). Data was collected from all 48 employees of the Dinas Perpustakaan dan Kearsipan using a saturated sampling technique. The analysis includes F-test to assess simultaneous influence and t-test to determine the partial effect of each variable. Findings: The results of the study show that teamwork, communication, and work environment simultaneously have a significant effect on employee performance, with a calculated F-value of 15.129, which is greater than the F-table value of 3.50. Furthermore, communication was found to have the most dominant influence on employee performance with the highest beta coefficient (5.727) and a significance value of 0.000, indicating a strong and significant effect. Conclusion: The study concludes that all three factors teamwork, communication, and work environment have a positive and significant impact on employee performance. Among these factors, communication plays the most significant role in improving performance. Novelty/Originality of this article: This research contributes to the literature on employee performance by providing insights into the specific influence of teamwork, communication, and work environment in a public sector context, particularly in libraries and archives offices. It also emphasizes the practical application of these findings to enhance organizational effectiveness.